Phellinus igniarius Polysaccharides Ameliorate Hyperglycemia by Modulating the Composition of the Gut Microbiota and Their Metabolites in Diabetic Mice - Zaizhong Ni; Jinting Li; Xinyi Qian; Yidan Yong; Mengmeng Wu; Yanan Wang; Wendi Lv; Simeng Zhang; Yifei Zhang; Ying Shao; Anhui Chen (Molecules, 2023)
Gut microbiota dysbiosis has been reported as a risk factor in the development of type 2 diabetes mellitus (T2DM). Polysaccharides from Phellinus igniarius (P. igniarius) possess various properties that help manage metabolic diseases; however, their underlying mechanism of action remains unclear. Therefore, in this study, we aimed to evaluate the effect of P. igniarius polysaccharides (SH-P) on improving hyperglycemia in mice with T2DM and clarified its association with the modulation of gut microbiota and their metabolites using 16S rDNA sequencing and liquid chromatography–mass spectrometry. Fecal microbiota transplantation (FMT) was used to verify the therapeutic effects of microbial remodeling. SH-P supplementation alleviated hyperglycemia symptoms in T2DM mice, ameliorated gut dysbiosis, and significantly increased the abundance of Lactobacillus in the gut. Pathway enrichment analysis indicated that SH-P treatment altered metabolic pathways associated with the occurrence and development of diabetes. Spearman’s correlation analysis revealed that changes in the dominant bacterial genera were significantly correlated with metabolite levels closely associated with hyperglycemia. Additionally, FMT significantly improved insulin sensitivity and antioxidative capacity and reduced inflammation and tissue injuries, indicating improved glucose homeostasis. These results indicate that the ameliorative effects of SH-P on hyperglycemia are associated with the modulation of gut microbiota composition and its metabolites.